Study of Clinical Characteristics of AIDS Patients With Opportunistic Infections: Findings From Cut Mutia General Hospital - Syahri, Alfi; Sukartini, Tintin Sukartini; Wahyuni, Erna Dwi; Sriyono, Sriyono; Zulkarnain, Hakim; Sudarmaji, Wikan Purwihantoro; Soares, Domingos; Fitria, Mawaddah; Rahmawati, Eti (Universitas Nahdlatul Ulama Surabaya, 2025)
Introduction: HIV/AIDS remains a global public health challenge, with opportunistic infections (OIs) being a major cause of morbidity and mortality. In resource-limited settings such as Aceh, Indonesia, the burden of OIs significantly impacts the management and outcomes of HIV/AIDS patients. Purpose: This study aims to describe the demographic and clinical characteristics, the prevalence of OIs, and treatment outcomes among HIV/AIDS patients treated at Cut Mutia General Hospital in Lhokseumawe, Aceh. Methods: A retrospective observational study was conducted using medical records of 55 HIV/AIDS patients treated between January 2023 and October 2024. Data included demographic profiles, clinical features, types of OIs, and treatment outcomes. Descriptive statistical analysis was performed. Results: The majority of patients were male (67.3%) and aged 25–44 years (81.8%). Oral candidiasis (28.1%) and pulmonary tuberculosis (17.7%) were the most common OIs. Notably, some patients experienced multiple OIs. Most patients (76.4%) were discharged in stable condition, while 23.6% succumbed to their illnesses. Conclusions: This study highlights the high prevalence of OIs among HIV/AIDS patients in Lhokseumawe, emphasizing the need for early detection, improved clinical management, and integrated care services. Targeted interventions are critical to reducing mortality and improving patient outcomes in resource-constrained settings.